It Takes a Team to Make It Through: The Role of Social Support for Survival and Self-Care After Allogeneic Hematopoietic Stem Cell Transplant - Song, Yaena; Chen, Stephanie; Roseman, Julia; Scigliano, Eileen; Redd, William H.; Stadler, Gertraud (Frontiers in Psychology, 2021)
Background: Social support plays an important role for health outcomes. Support for those living with chronic conditions may be particularly important for their health, and even for their survival. The role of support for the survival of cancer patients after receiving an allogeneic hematopoietic cell transplant (alloHCT) is understudied. To better understand the link between survival and support, as well as different sources and functions of support, we conducted two studies in alloHCT patients. First, we examined whether social support is related to survival (Study 1). Second, we examined who provides which support and which specific support-related functions and tasks are fulfilled by lay caregivers and healthcare professionals (Study 2). Methods: In Study 1, we conducted a retrospective chart review of alloHCT patients (N = 173, 42.8% female, age: M = 49.88) and registered availability of a dedicated lay caregiver and survival. In Study 2, we prospectively followed patients after alloHCT (N = 28, 46.4% female, age: M = 53.97, 46.4% ethnic minority) from the same hospital who shared their experiences of support from lay caregivers and healthcare providers in semi-structured in-depth interviews three to six months after their first hospital discharge. Results: Patients with a dedicated caregiver had a higher probability of surviving to 100 days (86.7%) than patients without a caregiver (69.6%), OR = 2.84, p = .042. Study 2 showed how important it was for patients after transplant to receive support due to their emotional needs and complex self-care regimen. The role of lay caregivers extended to many different areas of patients’ daily lives, including support for attending doctor’s appointments, managing medications and financial tasks, physical distancing, and maintaining strict dietary requirements. Healthcare providers mainly fulfilled medical needs and provided informational support, while lay caregivers were the main source of emotional and practical support. Conclusion: The findings highlight the importance of studying support from lay caregivers as well as healthcare providers, to better understand how they work together to support patients’ adherence to recommended self-care and survival. ref:_00D58JetR._5004K5WxnD:ref